Abatedouros de frango da microrregião de Pato Branco: características organizacionais, inovação tecnológica e uso da água sob a perspectiva do modelo de produção mais limpa - Weschenfelder, Francielle Zancanaro (2014)
This study aims to characterize the chicken slaughterhouses of Pato Branco microregion, analyzing the interfaces of their organizational characteristics, technological innovation and use of water, considering the environmental model of Cleaner Production. For its development, it was adopted the methodology of multicase analysis with a predominantly qualitative approach. As tools for collecting data in the field, semi structured questionnaires consisting of open and closed questions were applied by interview, as well as observations. The questionnaires were formulated based on the adaptation of questions from the Research and Innovation Questionnaire - PINTEC 2011. The results indicate that the sector is composed of medium- large - sized companies, formed by limited-liability company, corporation and a cooperative. Such companies processed on average 12,051 tonnes of chicken per month, being processed in natura meat (whole carcass) and value added products (cuts, offals and processed mixed meat) allocating 61 % of its production to domestic market and 39 % for foreign market. Looking at the period from 2010 to 2012 was observed that two of the three companies showed technological innovation activities in product and process (TPP), one focusing on products while the other focusing on processes, presenting both incremental and radical features of innovation to the performed activities. Analyzing the TPP innovations, some are directly related to water use and minimizing and recycling waste, being these innovations in the use of abdominal fat, the acquisition of machinery and equipment for automation and/or expansion of automation processes, changes in layout for better capturing of waste; practices in water control (locks and registration chokes and hydrometer; sprinkle nozzles, water reuse) and the total use of organic waste resulting from the production process. These actions had as a return for organizations: minimization of generated effluent, reduction in water use in the production process; higher profit margin in the recycling of waste for the manufacture of flour and oil to resale to third parties. It can be concluded that the chicken slaughterhouses of Pato Branco microregion succeeded to incorporate the assumptions of the Cleaner Production model to practices of water use and technological innovation concealing economic gains to environmental benefits.